PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS X SMK NEGERI 6 AMBON MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN MEDIA FLASH PLAYER PADA MATERI IKATAN KIMIA - Natalia Hingzty de Sirat; Carolina S Ayal; Y Manoppo (Molluca Journal of Chemistry Education (MJoCE), 2019)
This study aims to determine the increase in learning outcomes of students of SMK Negeri 6 Ambon by using the NHT coopertive learning model (Numbered Heads Together) with Flash Player media. The purpose of this research was to determine the improvement of learning outcomes in the chemical bonding material learning by using the NHT learning model on class X TI-2. This research was conducted with a study sample of 27 students in class X TI-2. Data collection is done by using test instruments and LKPD. The results of data analysis showed that the learning outcomes of class X TI-2 students achieved different qualifications, namely very good qualifications 1 (3.70%). Good 10 (37.04%), Sufficient 10 (37.04%), less 6 (22.22%). The N-gain achievement data obtained were 18 students (66.67%) in the high category and 9 students (33.33%) in the moderate gain category, overall the average n-gain value was 0.71 meant in the high category. Thus the NHT type cooperative learning model can help improve student learning outcomes